2012
DOI: 10.1107/s1744309112024372
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization studies of the murine c-di-GMP sensor protein STING

Abstract: The innate immune response is the first defence system against pathogenic microorganisms, and cytosolic detection of pathogen-derived DNA is believed to be one of the major mechanisms of interferon production. Recently, the mammalian ER membrane protein STING (stimulator of IFN genes; also known as MITA, ERIS, MPYS and TMEM173) has been found to be the master regulator linking the detection of cytosolic DNA to TANK-binding kinase 1 (TBK1) and its downstream transcription factor IFN regulatory factor 3 (IRF3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…To date, five structures of hSTING in apo and c-di-GMPbound forms have been reported (Huang et al, 2012;Ouyang et al, 2012;Shu et al, 2012;Su et al, 2012;Yin et al, 2012). Interesting, they all seem to adopt a similar set of open-form structures, which are different to the closed-form structures of mSTING that we have described in this manuscript.…”
Section: Why Do Hsting and Msting Adopt Different Apo And C-di-gmp-bomentioning
confidence: 63%
See 2 more Smart Citations
“…To date, five structures of hSTING in apo and c-di-GMPbound forms have been reported (Huang et al, 2012;Ouyang et al, 2012;Shu et al, 2012;Su et al, 2012;Yin et al, 2012). Interesting, they all seem to adopt a similar set of open-form structures, which are different to the closed-form structures of mSTING that we have described in this manuscript.…”
Section: Why Do Hsting and Msting Adopt Different Apo And C-di-gmp-bomentioning
confidence: 63%
“…The sample preparation for truncated mSTING and its complexes with c-di-GMP have been reported in a previous communication (Su et al, 2012). In brief, the full-length Mus musculus (mouse) STING gene was synthesized using a twostep PCR-based DNA-synthesis method using Escherichia coli optimized codons (Xiong et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of CDN-STING crystal structures along with recent results describing human STING allele-CDN dependent signaling relationships will facilitate structure-based studies to develop effective CDN compounds that activate innate immunity across genetically diverse human populations [Chin et al 2013; Huang et al 2012; Ouyang et al 2012; Shang et al 2012; Shu et al 2012; Su et al 2012]. Hydrogen bonding between CDN oxygen and phosphate atoms with amino acids at the interface of the STING homo-dimer binding cleft promotes its conformational transition and activate downstream signaling [Burdette and Vance, 2013].…”
Section: Cdn Synthesis and Design Of Compounds With Increased Potencymentioning
confidence: 99%
“…Transmembrane Protein 173 (TMEM173), also named stimulator of interferon genes (STING), is a transmembrane protein localized in endoplasmic reticulum[4]. Previous studies revealed that it played an important role in the innate immune response to viral and bacterial infections via regulating type-I IFN signaling and thereby innate immunity[5].…”
Section: Introductionmentioning
confidence: 99%